CCTV and robbery in high-rise public housing in Hong Kong. Issue 3 (16th July 2020) - Chow, Lina; Mawby, Rob I.
Abstract : Purpose: In Hong Kong, robberies occurring in the elevators in high-rise buildings were identified as a particular problem and the purpose of this paper is to address a dedicated programme aimed at reducing such offences. Design/methodology/approach: A comparison of elevator-based robbery statistics over a ten-year policy-implication period, in two police districts, one with a high rate of public ownership and a traditionally high rate of elevator robberies, the second with a higher rate of private ownership and a traditionally lower rate of such robberies. Findings: The evidence suggests that the programme was successful, with such robberies declining significantly and with no evidence of displacement. Research limitations/implications: This research is based on police statistics. There is a need for more research, for example, investigating residents' involvement with the system and the extent to which it encouraged shared ownership of the initiative. Practical implications: What is clear is that, where in the West the Newman legacy led to the demonisation of high-rise public sector housing, in Hong Kong, where there is no viable alternative, the use of CCTV helped transform such areas into safer communities. Social implications: The rate of robbery, most notably elevator-based robbery, fell dramatically, improving community safety. Originality/value: Though there has been a considerable amount of research on the impact of CCTV on crime, almost all of this has focussed on Western industrial societies and little of it has addressed robbery. To the best of authors' knowledge, this research is the first in Hong Kong, and the first to evaluate the impact of CCTV on robbery.